Identity Politics in the Construction of Electoral Laws: A Qualitative Analysis - Jukari, Ahmad; Karimullah, Suud Sarim; Muhajir, Muhajir (Universitas Islam Negeri Walisongo Semarang, 2023)
This article examines the construction of electoral regulations in Indonesia concerning representational and identity politics. Although Law No. 7 of 2017 on General Elections governs electoral processes to safeguard national identity and interests, gaps remain in addressing the legal dimensions of identity politics. This study aims to analyze how identity politics is constructed within Indonesia’s electoral law and to assess the extent to which these laws accommodate the principle of representation without fostering identity-based discrimination. Employing a non-doctrinal research method with a normative approach, this study utilizes documentation and literature analysis as its primary data sources. The findings reveal that electoral regulations are designed to make elections an instrument for protecting national identity and interests. While the Election Law does not explicitly incorporate regional, ethnic, or religious representation, its implementation reflects the influence of specific legal arrangements, such as those governing the Special Autonomy of Papua Province, the Aceh Government, and the Special Region of Yogyakarta. These special regulations provide limited space for representational politics based on regional, cultural, and religious affiliations. Furthermore, electoral regulations prohibit various campaign practices that may evoke or exploit identity politics. This study contributes to a deeper understanding of the dynamics between representation and identity politics within the legal framework of Indonesia’s electoral system. Artikel ini mengkaji konstruksi peraturan perundang-undangan pemilu di Indonesia dalam kaitannya dengan politik representasi dan politik identitas. Meskipun Undang-Undang No. 7 Tahun 2017 tentang Pemilihan Umum mengatur penyelenggaraan pemilu untuk menjaga identitas dan kepentingan nasional, masih terdapat kesenjangan dalam pengaturan dimensi hukum terkait politik identitas. Penelitian ini bertujuan untuk menganalisis bagaimana politik identitas dikonstruksikan dalam hukum pemilu Indonesia serta menilai sejauh mana regulasi pemilu mengakomodasi prinsip representasi tanpa menimbulkan diskriminasi berbasis identitas. Dengan menggunakan metode penelitian non-doktrinal melalui pendekatan normatif, penelitian ini memanfaatkan studi dokumentasi dan kepustakaan sebagai sumber data utama. Hasil penelitian menunjukkan bahwa regulasi pemilu dirancang untuk menjadikan pemilu sebagai instrumen dalam melindungi identitas dan kepentingan nasional. Meskipun Undang-Undang Pemilu tidak secara eksplisit memuat unsur representasi berdasarkan daerah, etnis, atau agama, implementasinya dipengaruhi oleh pengaturan khusus seperti Otonomi Khusus Provinsi Papua, Pemerintahan Aceh, dan Daerah Istimewa Yogyakarta. Pengaturan khusus tersebut memberikan ruang terbatas bagi praktik politik representasi berbasis daerah, budaya, dan agama. Selain itu, regulasi pemilu juga melarang berbagai bentuk kegiatan kampanye yang berpotensi menimbulkan atau mengeksploitasi politik identitas. Artikel ini berkontribusi dalam memperdalam pemahaman mengenai dinamika antara representasi dan politik identitas dalam kerangka hukum sistem pemilu di Indonesia. Keywords: General Election; Identity Politics; Legal Construction; Electoral Law.